Analysis of Thermal Sensitivity of Human Cytomegalovirus Assayed in the Conventional Conditions of a Human Milk Bank - Gayà, Antoni; Rittà, Massimo; Lembo, David; Tonetto, Paola; Cresi, Francesco; Sottemano, Stefano; Bertino, Enrico; Moro, Guido E.; Calvo, Javier; Donalisio, Manuela (Frontiers in Pediatrics, 2021)
One of the main concerns in human milk banks (HMB) is the transmission of human cytomegalovirus (HCMV) that could be present in the milk of infected women. There are consistent data showing that this virus is destroyed by Holder pasteurization (62.5 ºC for 30min), but there is a lack of information about the response of the virus to the treatment at lower temperatures in strict HMB conditions. In order to analyze the effectiveness of different temperatures of pasteurization to eliminate HCMV in human milk, a preliminary assay was performed incubating HCMV-spiked raw milk samples from donor mothers at tested temperatures in a PCR thermocycler and the viral infectivity was assayed on cell cultures. No signs of viral replication were observed after treatments at temperatures equal or greater than 53 °C for 30 min, 20 min and 10 min, 58 °C for 5 min, 59 °C for 2 min, and 60 °C for 1 min. These data were confirmed in a pasteurizer-like model introducing HCMV-spiked milk in disposable baby bottles. No viral infectivity was detected on cell cultures after heating treatment of milk for 30 min at temperatures from 56 °C to 60 °C. Thus, our results show that by using conventional pasteurization conditions, temperatures in the range of 56 ºC to 60 °C are enough to inactivate HCMV. Consequently, we consider that, in order to provide a higher quality product, the current recommendation to pasteurize both mother’s own milk and donated milk at 62.5 °C must be re evaluated.